The effect of unilateral training on contralateral limb power in young women and men - Andrzej Mastalerz; Jerzy Sadowski (Termedia Publishing House, 2021)
The purpose of this study was to determine the effect of training of one side of the body on the muscle torques and power output on the trained and untrained side. Seventeen female and twenty-two male students were subject to a four-week knee joint power training regimen on a specially designed stand. The subjects were divided into two groups: a training group (female - N = 11 and male - N = 16) and a control group (female - N = 6 and male - N = 6). Effectiveness of power training on the stand described previously was estimated based on bilateral knee torque and power under static and isokinetic conditions. The experiment lasted for 39 days and was preceded by preliminary studies (pre-training). Control measurements in training groups were made after four weeks of training (post-training) and after the next two weeks (de-training). Power training caused an insignificant increase in force and power in both groups for the untrained leg and a significant increase in RMS EMG. Therefore, the study confirmed the hypothesis that resistance training performed in dynamic conditions can affect the contralateral limb and may also trigger delayed adaptations to training conditions during the detraining phase. Sex differences in adaptation to power training are not clear; however, the differences in gains in contralateral effects between men and women were not confirmed.